Carboranes as Aryl Mimetics in Catalysis: A Highly Active Zwitterionic NHC‐Precatalyst. Issue 33 (7th April 2017) - Selg, Christoph; Neumann, Wilma; Lönnecke, Peter; Hey‐Hawkins, Evamarie; Zeitler, Kirsten
Abstract: Invited for the cover of this issue are the groups of Kirsten Zeitler and Evamarie Hey‐Hawkins at the University of Leipzig. The image depicts the carborane catalyst being a result of a long hatching process that eventually provides the starting point of a new member of the NHC‐catalyst family. Read the full text of the article at10.1002/chem.201700209 . Abstract : " We decided to approach this key issue from a completely new perspective by moving one group to the left in the periodic table from carbon to boron and employing carboranes as aryl mimetics ." Read more about the story behind the cover in the Cover Profile and about the research itself on page 7932 ff. (DOI:10.1002/chem.201700209 ).